Right of Speedy and Fair Trial of the Accused: The Impact of Delayed Justice on Society (Journal of Advances and Scholarly Researches in Allied Education, 2019)
“Justice delayed is justice denied” the aim of our justice delivery system is to provide justice to each and every individual of the society and if there is a delay in the delivery of justice that is considered as the denial of Justice. Delay in the delivery of Justice is much discussed issue. The recent incident in which the four persons who were facing the acquisition of the rape and murder of one veterinary doctor from shamshabad in Hyderabad were encountered by the police officers and the people were happy and celebrated the encounter, this happiness of the general public and their celebration is dangerous for the society as it indicates the anger against delay in the delivery of Justice. The makers of the constitution intends to secure the justice of the people as the Preamble of the Constitution shows the intention of the makers.-“we the people of India having solemnly resolved to constitute India into sovereign, socialist, secular, democratic, republic and to secure all its citizens justice, social, economic and political.” It is sad to say that after endless amendments in the constitution, people of our nation are still not able to get justice on time.